2019
DOI: 10.1111/jeb.13484
|View full text |Cite
|
Sign up to set email alerts
|

Population biology of a selfish sex ratio distorting element in a booklouse (Psocodea: Liposcelis)

Abstract: Arthropods harbour a variety of selfish genetic elements that manipulate reproduction to be preferentially transmitted to future generations. A major ongoing question is to understand how these elements persist in nature. In this study, we examine the population dynamics of an unusual selfish sex ratio distorter in a recently discovered species of booklouse, Liposcelis sp. (Psocodea: Liposcelididae) to gain a better understanding of some of the factors that may affect the persistence of this element. Females t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Strongly distorted sex ratios as observed here in A. lythri may be caused by genomic conflicts over sex chromosomes or sex-determining factors (Perlman et al 2015 ). Two types of selfish genetic elements are known to manipulate the sex of their hosts: cytoplasmic inherited endosymbionts (like Wolbachia , Rickettsia , Spiroplasma , and Cardinium ) and selfish genetic elements on sex chromosomes (Hodson and Perlman 2019 ). In addition, mitochondria as cytoplasmic elements may also benefit the female sex to the expense of males (Burt and Trivers 2006 ; Perlman et al 2015 ), as has been repeatedly shown for cytoplasmic male sterility in plants (He et al 2021 ; Wang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strongly distorted sex ratios as observed here in A. lythri may be caused by genomic conflicts over sex chromosomes or sex-determining factors (Perlman et al 2015 ). Two types of selfish genetic elements are known to manipulate the sex of their hosts: cytoplasmic inherited endosymbionts (like Wolbachia , Rickettsia , Spiroplasma , and Cardinium ) and selfish genetic elements on sex chromosomes (Hodson and Perlman 2019 ). In addition, mitochondria as cytoplasmic elements may also benefit the female sex to the expense of males (Burt and Trivers 2006 ; Perlman et al 2015 ), as has been repeatedly shown for cytoplasmic male sterility in plants (He et al 2021 ; Wang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…2). Liposcelis booklice, a genus with PGE and parthenogenesis, also has some females with only maternal genome transmission, most likely a type of hybridogenesis (Hodson & Perlman 2019;Hodson et al 2017;Mockford 1971) In many cases, new patterns of asymmetric inheritance emerge within clades that are already asymmetric. Examples include the co-occurence of PGE and germline restricted chromosomes in the gall midges and fungus gnats, or the B chromosomes in mealybugs which exploit the transmission asymmetry of PGE to enhance their own transmission.…”
Section: Origin and Taxonomic Distributionmentioning
confidence: 99%